Didactopathogenicity - Cukier, José (1996)
The author discusses the development of conditions generated by inappropriate teaching. The role of educacional institutions that support educators with .narcissistic personality is criticized. The characteristics of these type of educarors, their main defenses and che didactopathogenic interactions that are established between the teachers and the students are described. These generare passive/active transformation, taboo rhoughts, encyclopedic knowledge, posthumous memory, behavior disorders, lack of attention and marked aggressiveness. The concept of the teacher and his doubles is also discussed.